PERKAWINAN EKSOGAMI: LARANGAN PERKAWINAN SATU DATUAK DI NAGARI AMPANG KURANJI, SUMATERA BARAT - Putriyah, Nola; Wahib, Ahmad Bunyan (Al-Ahwal: Jurnal Hukum Keluarga Islam, 2015)
People of Nagari Ampang Kuranji implement exogamous marriage in the form of inter clan and kinship marriage. This exogamous marriage, however, are varies among the nagaris. The existence of datuak in every clan brings an effect to the possibility of a groom to have a bride from one clan under the condition of different datuak. Customary fines will be applied to those who trespasses this customary regulation. This article tries to elucidate exogamous marriage in Ampang Kuranji from the perspective of Islamic law. Utilizing ‘urf perspective, this article argues that exogamous marriage among people of Nagari Ampang Kuranji can be considered as ‘urf sahih, a customary tradition that is inline with Islamic teachings.